Respuesta :

[tex]\\ \rm\longmapsto \dfrac{x+3}{4}=\dfrac{x+6}{6}[/tex]

[tex]\\ \rm\longmapsto 6(x+3)=4(x+6)[/tex]

[tex]\\ \rm\longmapsto 6x+18=4x+24[/tex]

[tex]\\ \rm\longmapsto 6x-4x=24-18[/tex]

[tex]\\ \rm\longmapsto 2x=6[/tex]

[tex]\\ \rm\longmapsto x=3[/tex]

Answer:

[tex]\dashrightarrow \: { \tt{ \frac{x + 3}{4} = \frac{(x + 6)}{6} }} \\ \\\dashrightarrow \: { \tt{6(x + 3) = 4(x + 6)}} \\ \\ \dashrightarrow \: { \tt{6x + 18 = 4x + 24}} \\ \\ \dashrightarrow \: { \tt{6x - 4x = 24 - 18}} \\ \\ \dashrightarrow \: { \tt{2x = 6}} \\ \\ \dashrightarrow \: { \tt{x = \frac{6}{2} }} \\ \\ \dashrightarrow \: { \boxed{ \: \: x = 3 \: \: }}[/tex]

ACCESS MORE